ANALGESIC POWER TEST OF MAHOGANY LEAF EXTRACT (Swietenia mahagoni) ON MALE MICE (Mus musculus. L) - Linda Sari; Nur Mahdi; Ani Agustina (Journal of Pharmacology Experiment and Pharmaceutical Technology, 2025)
Mahogany leaves (Swietenia mahagoni) have flavonoids in them that might help with pain by stopping the cyclooxygenase enzyme from working. The purpose of this study is to see if compounds from mahogany leaves (Swietenia mahagoni) can help relieve pain in mice that have been given acetic acid. This study used the chemical stimulation method (writhing). Twenty-five mice were divided into 5 treatment groups, namely group 1 was given Na-CMC as a negative control, group 2 was given paracetamol at a dose of 1.3 mg/20 gBW as a positive control, and groups 3, 4, and 5 were given mahogany leaf extract (Swietenia mahagoni) at a dose of 2.8 mg/20 gBW, 5.6 mg/20 gBW, and 11.2 mg/20 gBW. Each group was given treatment orally; 30 minutes later, the mice were injected with 1% acetic acid intraperitoneally. Additionally, researchers observed and counted the number of wriggles every 15 minutes for a duration of 90 minutes. This study shows that the ethanol extract of mahogany leaves (Swietenia mahagoni) at a dose of 11.2 mg/20 g BB with a 100% success rate can relieve pain.